THE EFFECT OF THE LANGUAGE OF THOUGHT ON PRIVATE SPEECH PRODUCTION - Sarab, Mohammad Reza Anani; Gordany, Yahya (Indonesian Journal of Applied Linguistics, 2015)
Investigations into the application of foreign language to mediate psychological activity have produced contradictory results. The present paper reports two experiments designed to examine the influence of L1 and L2 on cognitive regulation and private speech production. Results indicate the important role that L1 plays in cognitive reasoning of the participants. Advanced participants, however, had significantly better performance when they used L2 for mental activity.Â  The language used for self-rgulation though, did not seem to relate to the amount of private speech produced. More proficient participants, on the other hand, seemed to produce qualitatively different kinds of L2 private speech. These findings indicate that it is necessary to consider quality, not just quantity, when studying constructs such as cognitive regulation, private speech production and the relations between them. In addition, findings have important practical implications for both language learners and instructors in creating more constructive language learning environments.